Dietary responses to a multiple sclerosis diagnosis: a qualitative study - Russell, R.; Black, Lucinda; Sherriff, Jill; Begley, Andrea (Nature Publishing Group, 2018)
Background/objectives: Multiple sclerosis (MS) is an immune-mediated disease with no known cure and insufficient evidence to support a special therapeutic diet to alter symptom management or disease progression. Several studies have reported dietary changes made by people with MS, but there has been limited investigation into experiences surrounding diet in those recently diagnosed. This study explored responses to diet after a recent diagnosis of MS in people living in Western Australia. Subjects/methods: Eleven adults with MS (mean time since diagnosis 8 months) participated in semi-structured interviews focusing on responses to diet since MS diagnosis. Interviews were transcribed, coded and analysed using grounded theory principles. Results: Three theme responses emerged; (1) the perceived incompatibility of lack of/or generalised dietary advice with disease seriousness at the time of diagnosis; (2) extensive personal research and information seeking with difficulty judging credibility, and (3) self-experimentation with diet to either control MS symptoms or to cure MS. Conclusions: Given the seriousness of the disease, there is a perceived gap in dietary information provided at the time of diagnosis. Healthcare professionals should address concerns with alternative therapeutic diets advertised to treat or cure MS, and clearly convey the reasoning for the general healthy dietary recommendations. This would better align advice with the perceptions about the role of diet in MS, assist people with MS in need of information and minimise dietary self-experimentation. Future research should explore the importance of diet for those who have had MS for a longer period of time.